The Development of a Social Work Program for an Islamic Day School in Southwestern Ontario - Siham Elkassem; Rick Csiernik (International Journal of School Social Work, 2018)
The Development of a Social Work Program for an Islamic Day School in Southwestern Ontario Abstract This article examines the evolution of a social work program for an Islamic Day School in London, Ontario, Canada. The Muslim Resource Centre for Social Support and Integration (MRCSSI), and London Islamic School (LIS) developed A Safe Space for Children (SPC) school social work program after extensive community consultation and feedback from leadership and school teachers revealed the need for mental health supports for students. A program implementation and evaluation design was developed by the MRCSSI in collaboration with the LIS and accepted by school administration and community stakeholders. The overarching objectives were to provide students with counselling services; develop school wide interventions, connect students and their families to mental health community resources while also providing ongoing professional development opportunities to teachers on issues relating to student mental health issues. The development of SPC its rooted in literature that reveals that this population is vulnerable to the stigma related to mental health, issues of acculturation, racism, and discrimination. The establishment of a social work program situated in a faith-based school that offers an overall understanding of cultural values and spirituality, aligns with best practices in social work. The project was grounded in a participatory democracy approach integrated with the civil society perspective, constructivist and critical race theoretical frameworks that guided the assessment and program design. Key Words: Canada, Children, Islam, Mental Health, Muslim, Participatory Democracy, School Social Work
Keywords: Canada; Children; Islam; Muslim; Mental Health; School Social Work